Exact treatment of exchange in Kohn-Sham band-structure schemes - Görling, Andreas (Physical Review B, 1996)
A Kohn-Sham (KS) scheme for solids treating exchange exactly is introduced. The scheme emerges from a recently introduced exact formal KS procedure [A. Görling and M. Levy, Phys. Rev. A 50, 196 (1994)]. The exact density-functional exchange potential is obtained in terms of its Fourier components. The method can easily be implemented on the basis of existing Hartree-Fock schemes for solids employing plane waves as basis sets.